2022
DOI: 10.1007/s10461-022-03622-8
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, Social Cohesion, and HIV Risk Among Sexual and Gender Minorities in Two Cities in Zimbabwe

Abstract: Though stigma is a recognized contributor to the disproportionate HIV burden among sexual and gender minorities (SGM) in sub-Saharan Africa, data describing this association among Zimbabwean SGM are limited. We examined relationships between SGM stigma and HIV and the potential for social cohesion to moderate the association among Zimbabwean men who have sex with men, transgender women, and genderqueer individuals. Consenting participants (n = 1511) recruited through respondent-driven sampling for a biobehavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
1
1
0
1
Order By: Relevance
“…This is reflected in the results which show that those in the community-led arm had over double (OR 2.08 95% CI 1.03–4.19) the odds of HIV self-testing compared to community-based arm in high social cohesion communities. This is aligned with previous research that has found higher social cohesion to increase HIV testing [ 10 , 23 ]. Literature has suggested that increased cohesion promotes trust and community empowerment which results in behaviour change.…”
Section: Discussionsupporting
confidence: 92%
“…This is reflected in the results which show that those in the community-led arm had over double (OR 2.08 95% CI 1.03–4.19) the odds of HIV self-testing compared to community-based arm in high social cohesion communities. This is aligned with previous research that has found higher social cohesion to increase HIV testing [ 10 , 23 ]. Literature has suggested that increased cohesion promotes trust and community empowerment which results in behaviour change.…”
Section: Discussionsupporting
confidence: 92%
“…Fourteen articles13 68–80 were partially intersectional stigma studies incorporating an intersectional approach to some elements of the analysis or presentation of their findings. We also identified 10 articles81–90 that studied multiple stigmas in a non-intersectional manner and 142 articles4 13 16–18 21 51 52 91–224 that studied one stigma in one population of SGM or studied one stigma in each of multiple populations (eg, SSSAB stigma only among MSM and transgender stigma only among TGW). A summary of each intersectional stigma study (n=21) appears in online supplemental file 2 and a summary of each non-intersectional stigma study (n=152) appears in online supplemental file 3.…”
Section: Resultsmentioning
confidence: 99%
“…Em outro momento, Miller et al (2022) comenta sobre o estigma, coesão social e risco de desenvolvimento de IST entre as minorias e, assim como já evidenciado no quadro sinóptico sendo um fator de risco, os autores salientam a importância do conhecimento dos profissionais, abastecidos de informações baseadas em evidência científica, repassadas de forma clara, ética e profissional mas além de tudo, com um olhar futurista para que o indicador de vulnerabilidade dessa população diminua a cada dia.…”
Section: Resultsunclassified